Partially bio-based poly(amide imide)s by polycondensation of aromatic diacylhydrazides based on lignin-derived phenolic acids and aromatic dianhydrides: synthesis, characterization, and computational studies - Kuhire, Sachin S.; Sharma, Pragati; Chakrabarty, Suman; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Two new bio-based diacylhydrazide monomers, namely, 4,4-(propane-1,3-diylbis(oxy))bis(3-methoxybenzohydrazide) and 4,4-(propane-1,3-diylbis(oxy))bis(3,5-dimethoxybenzohydrazide) were synthesized starting from lignin-derived phenolic acids, namely, vanillic acid and syringic acid. A series of poly(amide imide)s was synthesized by polycondensation of these diacylhydrazide monomers with commercially available aromatic dianhydrides. Poly(amide imide)s showed inherent viscosity in the range 0.44-0.56 dLg(-1) and exhibited good solubility in organic solvents. Poly(amide imide)s could be cast into transparent, flexible, and tough films from their N,N-dimethylacetamide solutions. Poly(amide imide)s showed 10% weight loss in the temperature range 340-364 degrees C indicating their good thermal stability. Glass transition temperature (T-g) of poly(amide imides)s were measured by DSC and DMA which were in the range 201-223 degrees C and 214-248 degrees C, respectively. The T-g values of poly(amide imide)s were dependent on the number methoxy substituents on aromatic rings of diacylhydrazide monomers. Molecular dynamics simulation studies revealed that chain rigidity is the dominant factor for observed trends in T-g. (c) 2017 Wiley Periodicals, Inc.
Keywords: Biobased Polymers; Computational studies; Glass-transaction temperature; lignin; Monomers; Plant oils; Polyimide; Reneable resources; Renewable resources; Step-growth polymers; structure-property relations; Sustanaible Polymers; Thermal night; Thermosetting resins; Vanillin

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

Evaluation of the adhesive properties of vanillin-derived polyhydroxy urethanes - Ghuge, Gorakh Hiraman; Kambikanam, Karthika Vayalachery; Nair, Kiran Sukumaran (Journal of Applied Polymer Science, 2023)
Poly(hydroxy urethanes) (PHUs) have been considered attractive and safer variants of conventional polyurethanes (PUs). To improve the prerequisites of green and sustainable chemistry herein, we propose the synthesis and utilization of cyclic carbonate monomers majorly derived from vanillin, a lignin derivative, and CO2 for the development of PHUs. Kinetic evaluation on the polymerization temperature ascertained 80 degrees C as the optimum condition for PHU synthesis. The structural evaluation of PHUs was carried out by various spectroscopic techniques, such as FTIR, (HNMR)-H-1, and C-13-NMR, molar masses were determined by gel permeation chromatography (Mn varied between 2500 and 11,100 g/mol), and thermal properties evaluated by differential scanning calorimeter (Tg in the ranges of 28-42 degrees C), and thermogravimetric analysis (stable above 180 degrees C). Since the PHUs are enriched with pendant hydroxyl groups on their backbone which can promote adhesion, lap shear studies on the aluminum substrate exhibited a maximum shear strength of 1.65 +/- 0.37 MPa. This study demonstrates an attractive and environment-friendly pathway for developing novel PHUs network using renewable biobased resources and further explores its applicability as adhesives.
Keywords: adhesive; biobased cyclic dicarbonate; diamines; poly(hydroxyurethane)s; Vanillin

Recyclable l-glutamic acid-based polyester schiff base cross-linker for 3D printing applications - Kamble, Ganesh N.; Ghute, Aaditi P.; Asha, S. K. (ACS Applied Polymer Materials, 2026)
An l-amino acid-based polyester Schiff base cross-linker was developed from amine-functionalized polyester and biobased methacrylate vanillin. Vanillin, one of the few biobased and aromatic compounds readily available on an industrial scale, has recently garnered significant attention from the polymer community. The l-amino acid-based polyester Schiff base cross-linker (P3) was synthesized by condensing the aldehyde group of methacrylate vanillin with the amine group of the l-glutamic acid polyester. This polymeric cross-linker was used in resin formulations consisting of isobornyl acrylate as a reactive diluent and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as the photoinitiator for digital light processing (DLP) three-dimensional (3D) printing. The resulting 3D-printed parts exhibited good mechanical properties, with a Young's modulus of 1.5 GPa, and high thermal stability, with a T max of 410 degrees C. The chemical degradability of the 3D-printed materials was demonstrated in a mixture of tetrahydrofuran and diethylene triamine (1:1) at 80 degrees C for 48 h. The reusability of the recovered resin was demonstrated by adding fresh methacrylate vanillin and photoinitiator, followed by 3D printing using a DLP 3D printer. The 3D-printed parts produced from the recycled resin retained substantial mechanical properties, with a Young's modulus of 1.39 GPa, and thermal stability, with a T max of 390 degrees C.
Keywords: 3D printing; chemical degradation; covalent adaptable network; l-glutamicacid; Vanillin

Vanillin-based recyclable thermosets and their glass fiber reinforced composites - Veetil, Ashwani Puthiya; Ravikumar, Aniruddha; Rajput, Tejas; Singh, Aman Kumar; Thakur, Tamanna; Krishna, Abhijith; Pol, Harshawardhan; Shanmuganathan, Kadhiravan; Asha, S. K. (Macromolecular Chemistry and Physics, 2026)
The accumulation of end-of-life plastic materials and composite reinforcement waste materials has brought much attention to developing sustainable alternatives and their re-processability. Incorporating covalent adaptable networks (CANs) into the crosslinked network bridges the concept of reversibility into the otherwise conventional non-reversible networks. This study investigates the structure-property relation in two reversible hardener systems derived from vanillin using Schiff base chemistry. The ``CAN'' systems were synthesized by condensation of vanillin with two amines, 4,4'-oxydianiline and tris(2-aminoethyl)amine, respectively, to form Va_ODA and Va_TAEA. The epoxy thermosets exhibited glass transition temperatures (T-g) of 125 degrees C and 115 degrees C, respectively, for Va_ODA and Va_TAEA, which is superior to most reversible vanillin-based systems reported. The vitrimer-thermosets exhibited promising mechanical and thermal properties, and reshaping abilities as a function of applied temperatures, indicating the dynamic nature of linkages. Chemical degradability was demonstrated by heating to 80 degrees C for 12 h in aqueous acidic medium or excess amine. The fabricated glass fiber composites exhibited good mechanical properties with tensile strength of 361 MPa and degradability in acetic acid/water mixture with a fiber recovery of >98 %. The recovered glass fiber exhibited almost similar tensile strength as the virgin glass fiber, demonstrating its potential reusability. The epoxy vitrimers underwent mechanical reprocessing through hot-pressing, as well as chemical reprocessing via 3D printing and by regeneration of imine bonds to form an epoxy resin.
Keywords: 3D printing; covalent adaptable network; re-processability; Schiff base; Vanillin